Medidas de Espectroscopia Raman em cristais de DL-Valina a altas pressões - Rêgo, Fellipe dos Santos Campêlo (2015)
In this work, we present a study of the Raman scattering of DL-valine crystals (C5H11NO2) at room temperature under high hydrostatic pressures conditions using the spectral range of 40-3200 cm-1. Based on previous studies using Raman spectroscopy on crystals of DL-valine and other amino acids such as L-valine, L-isoleucine and L- asparagine, we proposed the classification of the bands in different vibration modes. The Raman spectrum obtained as function of pressure suggests that DL-valine suffered two structural phase transitions by 19,4 GPa. The first transition phase of between 1,4 GPa and 1,8 GPa where we observed the disappearance of three modes, one network mode and two internal modes classified as rocking of NH3+ and symmetric stretching of CH3, vs (CH3). The second phase transition of between 7,8 GPa and 8,8 GPa, where we observe the unfolding of a network mode, the disappearance of the internal mode associated with skeletal deformation, d(esk) and the splitting designated as CH2, v(CH2).